UPAYA MEMBANGUN KEARIFAN LOKAL MELALUI PARADIGMA SADAR WISATA (Studi Khasus : Di Desa Sendang Dhuwur, Kecamatan Paciran, Kabupaten Lamongan) - Budi Santoso, Mohammad Syafii (TIJAROTANA : Jurnal Ekonomi Dan Bisnis Syariah, 2020)
The study starts from the fact that Indonesia has manyamazing tourism. The tomb of Sunan Sendang in Lamonganparticularly has beautiful temples, unique culture and varioustempting traditional arts. Their attractions become a potential todevelop and it will bring advantages for the society. Byexploring and developing local wisdom, we can decrease andavoid the poverty since the natural source is conserved for thenext generation. Local wisdom contains norms and social valueswhich regulate the balance of natural source support and humanlife style and needs. Therefore, it should be inseparated part ofpolicy against poverty. Beside a structural approach, we canexplore local society life. The development of tourism villageleads to vary activities in the village and open a wide workfieldfor the society.The study aims to (1) describe the efforts to build localwisdom (2) describe the effort to build tourism awarenessparadigm to develop tourism village, (3) to find supporting andinhibiting factors in developing tourism village.The researcher employed a qualitative approach usingcase study design. Data collection was done using in-depthinterview, participative observation, and documentation. Dataanalysis technique included data reduction, data presentationand conclusion drawing. To check data validity, the researcherused source and method triangulation. The informants were thevillage chief, the family of Sunan Sendang, the head ofPokdarwis, the committee of Pokdarwis, the members ofPokdarwis and the society. The result shows that (1) the effortsto build local wisdom should involve the society, governmentand private parties in developing tourism village. Creating aPokdarwis becomes a solution for the village society andgovernment in building local wisdom to be a tourism attraction;(2) In building tourism awareness, it is important to have aparticular organization and governemnt support to provideassistance, training and guidance for the society to developtourism awareness in the village of Sendang Duwur ; (3) Thesupporting factor in developing tourism village is the supportfrom central, local and village government. Meanwhile, theinhibiting factor are the society apatism and businesscompetition among batik and gold enterpreneurs.